2015
DOI: 10.1002/jcp.24944
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of miR‐29s Affects the Lactation Activity of Dairy Cow Mammary Epithelial Cells

Abstract: Milk is important for human nutrition, and enhanced milk quality has become a major selection criterion for the genetic improvement of livestock. Epigenetic modifications have been shown to be involved in mammary gland development; but the mechanisms underlying their effects remain unknown. MicroRNAs are involved in the regulation of milk synthesis and in mammary gland development. Our study is the first to investigate the roles of miR-29s and epigenetic regulation in dairy cow mammary epithelial cells (DCMECs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 44 publications
1
59
0
1
Order By: Relevance
“…Bian et al [122] showed that miRNA-29s regulate the DNA methylation level by inversely targeting both DNMT3A and DNMT3B in dairy cow MECs. The inhibition of miRNA-29s caused global DNA hypermethylation and increased the methylation levels of the promoters of important lactation-related genes, including casein-α s1 ( CSN1S1 ), E74-like factor 5 ( ELF5 ), PPARγ ( PPARG ), sterol regulatory element binding protein-1 ( SREBP1 ), and glucose transporter-1 ( GLUT1 ).…”
Section: Epigenetic Regulation Of Lactationmentioning
confidence: 99%
See 2 more Smart Citations
“…Bian et al [122] showed that miRNA-29s regulate the DNA methylation level by inversely targeting both DNMT3A and DNMT3B in dairy cow MECs. The inhibition of miRNA-29s caused global DNA hypermethylation and increased the methylation levels of the promoters of important lactation-related genes, including casein-α s1 ( CSN1S1 ), E74-like factor 5 ( ELF5 ), PPARγ ( PPARG ), sterol regulatory element binding protein-1 ( SREBP1 ), and glucose transporter-1 ( GLUT1 ).…”
Section: Epigenetic Regulation Of Lactationmentioning
confidence: 99%
“…The inhibition of miRNA-29s reduced the secretion of lactoprotein, triacylglycerols and lactose by dairy cow MECs. The treatment of dairy cow MECs with 5-aza-2′-deoxycytidine decreased the methylation levels of the MIR29B promoter and increased the expression of miRNA-29b [122]. The enhancement of lactation activity and milk yield was thus associated with upregulation of DNMT3A- and DNMT3B-targeting miRNA-29s.…”
Section: Epigenetic Regulation Of Lactationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the likely more inhibited, the miRNA29b has strong epigenetic effects on the expression of several lactogenic genes [62], let-7a-5p is highly expressed in cow mammary [63], and miRNA1 has a strong control in the expression of β-lactoglobulin [64]. …”
Section: Resultsmentioning
confidence: 99%
“…MiR-486 regulation of lactation by targeting the PTEN gene in cow MGs has been demonstrated [87]. Bian et al [88] recently reported that epigenetic regulation of miR-29s affects the lactation activity of BMEC. MiR-181a was shown to regulate the biosynthesis of bovine milk fat through targeting acyl-CoA synthetase long-chain family member 1 (ACSL1) [89].…”
Section: Functional Validation Of Microrna Target Genesmentioning
confidence: 99%